How to study art worlds on the societal functioning of aesthetic values - Maanen, Hans van ([Amsterdam] Amsterdam University Press, 2009)
This necessary and thought-provoking study brings together the organisational side of the world of the arts and the understanding of the many functions art fulfi lls in our culture. The author sets out to establish how the organisation of art worlds serves the functioning of the arts in society. The book is divided into three sections, the first of which presents a comparative study of approaches to the art world as practiced by Dickie, Becker, Bourdieu, Heinich, and Luhmann, among others. The second part focuses on the philosphical debates concerning 'aesthetic experience'. Besides Kant, scholars such as Gadamer, Foster, Shustermann, Schaeffer and Carroll come to the fore. In the third part, the author traces the consequences of these theoretical approaches for the organization of art world practices.
Electronic reproduction.
Keywords: Art and society; Aesthetics -- Social aspects; Art -- Philosophy; Electronic books